Threatened Plant Translocation for Mitigation: Improving Data Accessibility Using Existing Legislative Frameworks. An Australian Case Study - Doyle, Chantelle A.; Pellow, Belinda J.; Bell, Stephen A. J.; Reynolds, Deborah M.; Silcock, Jennifer L.; Commander, Lucy E.; Ooi, Mark K. J. (Frontiers in Conservation Science, 2022)
Translocation of plants is used globally as a conservation action to bolster existing or establish new populations of threatened species and is usually communicated in academic publications or case studies. Translocation is also used to mitigate or offset impacts of urbanisation and development but is less often publicly published. Irrespective of the motivation, conservation or mitigation, on ground actions are driven by overriding global conservation goals, applied in local or national legislation. This paper deconstructs the legislative framework which guides the translocation process in Australia and provides a case study which may translate to other countries, grappling with similar complexities of how existing legislation can be used to improve accessibility of translocation records. Each year, across Australia, threatened plants are being translocated to mitigate development impacts, however, limited publicly accessible records of their performance are available. To improve transparency and opportunities to learn from the outcomes of previous mitigation translocations, we propose mandatory recording of threatened plant translocations in publicly accessible databases, implemented as part of development approval conditions of consent. The contribution to these need not be onerous, at a minimum including basic translocation information (who, what, when) at project commencement and providing monitoring data (outcome) at project completion. These records are currently already collected and prepared for translocation proposals and development compliance reporting. Possible repositories for this information include the existing national Australian Network for Plant Conservation translocation database and existing State and Territory databases (which already require contributions as a condition of licensing requirements) with new provisions to identify and search for translocation records. These databases could then be linked to the Atlas of Living Australia and the Australian Threatened Plant Index. Once established, proposals for mitigation translocation could be evaluated using these databases to determine the viability of mitigation translocation as an offset measure and to build on the work of others to ensure better outcomes for plant conservation, where translocations occur.